Whole-Genome Resequencing to Evaluate Life History Variation in Anadromous Migration of Oncorhynchus mykiss - Collins, Erin E.; Romero, Nicolas; Zendt, Joseph S.; Narum, Shawn R. (Frontiers in Genetics, 2022)
Anadromous fish experience physiological modifications necessary to migrate between vastly different freshwater and marine environments, but some species such as Oncorhynchus mykiss demonstrate variation in life history strategies with some individuals remaining exclusively resident in freshwater, while others undergo anadromous migration. Since there is limited understanding of genes involved in this life history variation across populations of this species, we evaluated the genomic difference between known anadromous (n=39) and resident (n=78) Oncorhynchus mykiss collected from the Klickitat River, WA, USA with whole-genome resequencing methods. Sequencing of these collections yielded 5.64 million single nucleotide polymorphisms (SNPs) that were tested for significant differences between resident and anadromous groups along with previously identified candidate gene regions. While a few regions of the genome were marginally significant, there was one region on chromosome Omy12 that provided the most consistent signal of association with anadromy near two annotated genes in the reference assembly: COP9 signalosome complex subunit 6 (CSN6) and NACHT, LRR and PYD domains-containing protein 3 (NLRP3). Previously identified candidate genes for anadromy within the inversion region of chromosome Omy05 in coastal steelhead and rainbow trout were not informative for this population as shown in previous studies. Results indicate that the significant region on chromosome Omy12 may represent a minor effect gene for male anadromy and suggests that this life history variation in Oncorhynchus mykiss is more strongly driven by other mechanisms related to environmental rearing such as epigenetic modification, gene expression, and phenotypic plasticity. Further studies into regulatory mechanisms of this trait are needed to understand drivers of anadromy in populations of this protected species.